2018
DOI: 10.1111/bcp.13490
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of causality assessment of herb–drug interactions in patients

Abstract: The aim of this review was to assess the severity of adverse drug reactions (ADRs) due to herb-drug interactions (HDI) in patients taking herbs and prescribed medications based on published evidence. Electronic databases of PubMed, the Cochrane Library, Medline and Scopus were searched for randomized or nonrandomized clinical studies, case-control and case reports of HDI. The data were extracted and the causal relationship of ADRs as consequences of HDI assessed using Horn's drug interaction probability scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 112 publications
1
75
0
3
Order By: Relevance
“…Herbal medicines and other botanicals are often used as complementary and alternative medicines which are believed safe, also has no strict safety and effective standards, should be paid great attention (Moreira et al, 2014;Lee et al, 2015;Alamgir, 2017;Cho et al, 2017;Cecilia and Orish, 2018;Jing and Teschke, 2018;Teschke et al, 2018). Herb-induced liver injury (HILI) refers to liver damage caused by TCMs, natural medicines and related preparations, resulting in adverse reactions such as dermatitis, nausea, vomiting, diarrhea, thrombocytopenia, coagulopathy, mental state changes, hepatotoxicity, nephrotoxicity, and electrolyte imbalance (Dag et al, 2014;Divya et al, 2016;Ming et al, 2017;Awortwe et al, 2018). However, the degree of HILI varies among different countries and regions (Zhou et al, 2013;Navarro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicines and other botanicals are often used as complementary and alternative medicines which are believed safe, also has no strict safety and effective standards, should be paid great attention (Moreira et al, 2014;Lee et al, 2015;Alamgir, 2017;Cho et al, 2017;Cecilia and Orish, 2018;Jing and Teschke, 2018;Teschke et al, 2018). Herb-induced liver injury (HILI) refers to liver damage caused by TCMs, natural medicines and related preparations, resulting in adverse reactions such as dermatitis, nausea, vomiting, diarrhea, thrombocytopenia, coagulopathy, mental state changes, hepatotoxicity, nephrotoxicity, and electrolyte imbalance (Dag et al, 2014;Divya et al, 2016;Ming et al, 2017;Awortwe et al, 2018). However, the degree of HILI varies among different countries and regions (Zhou et al, 2013;Navarro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of regulation in this field of treatment agents suggests caution with use of herbs in the context of NAFLD. Also, the lack of research indicates the possibility of drug interactions or adverse effects [ 158 , 159 , 160 , 161 ]. Herb–drug interactions have already been noted in warfarin, aspirin, alkylating agents, and cyclosporine, leading to toxicity in patients [ 158 , 161 ].…”
Section: Safety Concerns For Herb Supplementationmentioning
confidence: 99%
“…The gourd is reputed to maintain a healthy digestive tract by maintaining the microbiome balance, improving metabolism and preventing renal disease. 1 A recent study has confirmed that the gourd also has antidiabetic properties. 2 The authors reported that the gourd extracts had a significant impact on several markers of diabetes.…”
mentioning
confidence: 94%
“…1 The patients in the 50 published studies suffered from a variety of diseases including cancer, cardiovascular disease and kidney transplants. These patients were prescribed alkylating agents, warfarin and cyclosporine respectively.…”
mentioning
confidence: 99%